Evaluation of Parallelism of ala-tragus plane and occlusal plane - M Bonakdarchiyan; A Mottaghi; S Sahraneshin (Isfahan University of Medical Sciences, 2008)
Introduction: Occlusal plane orientation is an important part of organized occlusion. The ala-tragus plane is considered to be parallel to the occlusal plane while reconstructing occlusion. This study was aimed to determine the condition of parallelism of these two planes in Iranian.Methods and material: In this cross sectional study, 197 patients were examined. The angle between ala-tragus and occlusal plane was assessed by indexed fox plane and the position of Stensen's duct to adjacent molar in maxillary tooth and the position of the dorsal side of the tongue relative to posterior mandibular teeth were also examined by clinical examination. Then two planes were investigated by lateral cephalometry for 23 patients. Deep bite, long face, and with bruxism patients were identified to examine the probable effect of this position in them. The data was analyzed with t-test, Peirson and χ2 tests (a = 0.05).Results: The ala-tragus line had the tendency to be paralleled with posterior occlusal plane and the mean angle of two planes was 1.77˚. In cephalometric measurement, the estimated mean of the angle was 2.96˚. In the most of the cases, Dorsum of tongue was above the mandibular occlusal plan. In the half of the cases Stensen's duct was in the occlusal third of adjacent molar. Conclusion: The differences in the mean angles of clinical measurement and cephalometric measurement have been resulted from the differences in two methods. The results allow clinicians to parallel occlusal plan with the ala-tragus line to achieve a natural position for reconstruction of occlusal plan.Keywords: Dental Prosthesis, Dental Occlusion, Jaw Relation Record, Dental Radiography, Cephalometry